Electron and Proton Flux for Carbon Dioxide Reduction in Methanosarcina barkeri During Direct Interspecies Electron Transfer - Holmes, Dawn E.; Rotaru, Amelia-Elena; Ueki, Toshiyuki; Shrestha, Pravin M.; Ferry, James G.; Lovley, Derek R. (Frontiers in Microbiology, 2018)
Direct interspecies electron transfer (DIET) is important in diverse methanogenic environments, but how methanogens participate in DIET is poorly understood. Therefore, the transcriptome of Methanosarcina barkeri grown via DIET in co-culture with Geobacter metallireducens was compared with its transcriptome when grown via H2 interspecies transfer (HIT) with Pelobacter carbinolicus. Notably, transcripts for the F420H2 dehydrogenase, Fpo, and the heterodisulfide reductase, HdrABC, were more abundant during growth on DIET. A model for CO2 reduction was developed from these results in which electrons delivered to methanophenazine in the cell membrane are transferred to Fpo. The external proton gradient necessary to drive the otherwise thermodynamically unfavorable reverse electron transport for Fpo-catalyzed F420 reduction is derived from protons released from G. metallireducens metabolism. Reduced F420 is a direct electron donor in the carbon dioxide reduction pathway and also serves as the electron donor for the proposed HdrABC-catalyzed electron bifurcation reaction in which reduced ferredoxin (also required for carbon dioxide reduction) is generated with simultaneous reduction of CoM-S-S-CoB. Expression of genes for putative redox-active proteins predicted to be localized on the outer cell surface was higher during growth on DIET, but further analysis will be required to identify the electron transfer route to methanophenazine. The results indicate that the pathways for electron and proton flux for CO2 reduction during DIET are substantially different than for HIT and suggest that gene expression patterns may also be useful for determining whether Methanosarcina are directly accepting electrons from other extracellular electron donors, such as corroding metals or electrodes.